2008
DOI: 10.1073/pnas.0807102105
|View full text |Cite
|
Sign up to set email alerts
|

COPI coat assembly occurs on liquid-disordered domains and the associated membrane deformations are limited by membrane tension

Abstract: Cytoplasmic coat proteins are required for cargo selection and budding of tubulovesicular transport intermediates that shuttle between intracellular compartments. To better understand the physical parameters governing coat assembly and coat-induced membrane deformation, we have reconstituted the Arf1-dependent assembly of the COPI coat on giant unilamellar vesicles by using fluorescently labeled Arf1 and coatomer. Membrane recruitment of Arf1-GTP occurs exclusively on disordered lipid domains and does not indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 35 publications
(49 reference statements)
7
69
0
Order By: Relevance
“…Curved membranes tend to exclude sphingolipids and are enriched in phospholipids. For instance, in vitro reconstitution of COPI budding has shown that phase transition of phospholipid enriched domains is prevented at bud sites [49]. Phospholipid transfer proteins, flippases, PIPs, and, DAG also play important roles in the dynamic organization of the Golgi complex but are beyond the scope of this review [55, 78, 8187].…”
Section: Pla and Lpat Enzymes Remodel Phospholipids And The Golgi Commentioning
confidence: 99%
“…Curved membranes tend to exclude sphingolipids and are enriched in phospholipids. For instance, in vitro reconstitution of COPI budding has shown that phase transition of phospholipid enriched domains is prevented at bud sites [49]. Phospholipid transfer proteins, flippases, PIPs, and, DAG also play important roles in the dynamic organization of the Golgi complex but are beyond the scope of this review [55, 78, 8187].…”
Section: Pla and Lpat Enzymes Remodel Phospholipids And The Golgi Commentioning
confidence: 99%
“…Although accumulation of proteins and lipids at curvature is observed in a variety of experiments [23,29,30,31,32,33], single molecules have demonstrably different behavior [33]. So far, single proteins have not been observed accumulating at curvature, suggesting that a cluster of molecules is needed for accumulation or that the affinity for curvature is quite low and hard to observe in single molecule experiments, where the concentration is inherently low.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids that form liquidordered phases, such as sphingomyelin and cholesterol, and are abundant at the plasma membrane, are excluded from COPI-coated vesicles (Brügger et al, 2000). In in vitro reconstituted systems, Arf1-GTP and COPI assemble on liquid-disordered domains, and protect them from undergoing phase separation, suggesting that COPI assists lipid sorting during coat polymerization (Manneville et al, 2008).…”
Section: Interplay Between Cargo and The Copi Coatmentioning
confidence: 99%